Anaerobic prokaryotic processes drive manganese release in a drinking water reservoir - Hahn, Lea; Vriesen, Solveig Tabea; Packroff, Gabriele; Meier, Jutta; Manz, Werner (Frontiers in Microbiology, 2025)
IntroductionElevated manganese (Mn) concentrations in drinking water reservoirs present challenges for raw water treatment. During thermal stratification, a shift from oxic to anoxic conditions at the sediment-water interface intensifies the release of dissolved Mn into the water column.MethodsHigh-throughput amplicon sequencing of 16S rRNA genes was used to identify the prokaryotic community in sediments of the Wahnbach Reservoir, examining abundance, diversity, and potential metabolic processes concerning key physicochemical parameters. In addition, cultivation-based methods clarified the role of Mn cycling and related biogeochemical processes.ResultsSediment analyses revealed high sedimentary Mn contents and elevated Mn2+ concentrations in pore water. Bioinformatic analysis of 16S rRNA gene sequences revealed a diverse prokaryotic community involved in Mn cycling and competing redox processes, both in sediment samples and enrichment cultures selective for Mn-transforming organisms. Dominant metabolic processes included anaerobic respiration, such as methanogenesis and the reduction of Mn, Fe, sulfate, as well as nitrate, alongside oxidative processes like nitrification and methanotrophy. Cultivation-based approaches confirmed the relevance of these processes and uncovered interconnections among them through the enrichment of specific genera, including Rhodoferax, a typical Mn reducer, Ellin6067, an ammonium oxidizer, and the methanogen Methanosarcina.DiscussionSeasonal oxygen depletion promotes the release of Mn and Fe from sediments, with Mn(IV) and Fe(III) reduction occurring under increasingly reducing conditions and contributing to metal cycling and redox zonation. This study highlights the dynamic interaction between physicochemical gradients and prokaryotic community structure that drives Mn transformation in stratified freshwater systems.